RESPONS ANAK TERHADAP CERITA RAKYAT MALIN KUNDANG - Yulinda Indriani (JURNAL ILMIAH BAHASA DAN SASTRA, 2018)
Reception study is a review of literature relating to the acceptability of the reader, reception in the research and study of children’s literature there are several theories about the nature of literature and its reception horizon approach and its reader, study psychology literature has a functional relationship to the reception of literature, the reader psychology and child psychology reader. Theories abaout the nature of children’s literature , children’s literature begins with some types of children’s literature. Research of literature, namely the study of the reception of literature that analyzes the child’s response to foklore Malin Kundang. reason researchers use the story of Malin Kundang is favored by many people ranging from children to adults, other than that a lot of the mandate contained in the story of Malin Kundang. Key words : the reception of literature, children’s literature, folklore